Impact of Land Use and Transport Interaction on Transmition of COVID-19 in Jakarta - Nur Andina, Fathiyyah; Ratnasari Rakhmatulloh, Anita; Intan Kusumo Dewi, Diah (Universitas Ibn Khaldun Bogor, 2022)
Land use and transportation are well known to interact and influence one another. The COVID-19 pandemic is the global health crisis. The world faces difficulties managing disasters while making efforts to slowing the spread of COVID-19. The COVID-19 pandemic spreads quickly through physical contact, making it easy to spread in public places. The purpose of this study to determine the effects of land use and transportation interactions on COVID-19 transmission. The quantitative descriptive analysis and spatial statistical methods in Geographic Information Systems (GIS) have been used in this study. Descriptive analysis to describe data related to land use characteristics in the research area. Spatial Statistical Method in GIS to analyze data from both structured and spatial observations. Cross-checking the land use from Google Street View around the bus stop within a 400 meter radius with the existing land use directly yielded the observations. The findings revealed that the type of land use demonstrated an intensity of activity that had a high potential for spreading COVID-19 because at the bus stop with land use around the trading center, shopping centers, and office buildings that have a high activity intensity, it appears that they have a high positive number of COVID-19